Developing an E-Portfolio Model for Malaysian Skills Certification - Rahim, Mohd Bekri; Yunus, Faizal Amin Nur bin; masran, Saiful Hadi bin; Marian, Mohd Fairuz; Abd Baser, Jamil Bin; Azimat Ali, & Mohammad Musab (Journal of Technical Education and Training, 2019)
The rapid development of ICT nowadays demands that the vocational education system in Malaysia needs to change for improvement in the quality of technology-based learning systems. The Malaysia Skills Certification (MSC) E-portfolio model was developed in this study to improve the existing portfolio used for MSC purposes. This study was conducted to verify the MSC E-portfolio measurement model. Respondents involved in this study were 350 MSC instructors from Institute of Public Skills Training in Malaysia, where 200 respondents were selected from institution under the Ministry of Human Resources and 150 respondents were under the Ministry of Youth and Sports in Malaysia. The total size of the respondent is based on the sample size formula of Krejcie and Morgan and the sample was determined using a stratified random sampling method. A questionnaire was used to obtain the research data. Rasch measurement model approach using Winsteps software was used to carry out questionnaire checks in terms of reliability and the validity of the instrument. Verification of content validity and reliability is done by 7 experts through a modified Delphi method. All 38 indicators that measure the MSC E-portfolio elements have high reliability and validity based on internal consistency analysis, indicator reliability, convergent validity and discriminant validity. This shows that a combination of all these four elements can produce an E - portfolio system that is more systematic and multi-purpose, as the concept of e-portfolios are still least applied in the education system. Overall, it can be concluded that the E-portfolio MSC constructs influenced by four major factors which are, operating systems, assessment of competence, Recognition of Prior Achievement (RPA) and virtual learning space. This study also directly gives a new dimension to the MSC system from the aspect of student competency assessment, interactive learning, safety safer storage of learning materials and provide a more systematic knowledge management space.